Fc-fusion proteins and FcRn: structural insights for longer-lasting and more effective therapeutics. (June 2015) - Rath, Timo; Baker, Kristi; Dumont, Jennifer A.; Peters, Robert T.; Jiang, Haiyan; Qiao, Shuo-Wang; Lencer, Wayne I.; Pierce, Glenn F.; Blumberg, Richard S.
Abstract Nearly 350 IgG-based therapeutics are approved for clinical use or are under development for many diseases lacking adequate treatment options. These include molecularly engineered biologicals comprising the IgG Fc-domain fused to various effector molecules (so-called Fc-fusion proteins) that confer the advantages of IgG, including binding to the neonatal Fc receptor (FcRn) to facilitate in vivo stability, and the therapeutic benefit of the specific effector functions. Advances in IgG structure-function relationships and an understanding of FcRn biology have provided therapeutic opportunities for previously unapproachable diseases. This article discusses approved Fc-fusion therapeutics, novel Fc-fusion proteins and FcRn-dependent delivery approaches in development, and how engineering of the FcRn–Fc interaction can generate longer-lasting and more effective therapeutics.